Flash Synthesis and Continuous Production of C-Arylglycosides in a Flow Electrochemical Reactor - Takumi, Masahiro; Nagaki, Aiichiro (Frontiers in Chemical Engineering, 2022)
Electrochemistry provides a green and atom-efficient route to synthesize pharmaceutical and useful functional molecules, as it eliminates the need for the harsh chemical oxidants and reductants commonly used in traditional chemical reactions. To promote the implementation of electrochemical processes in the industry, there is a strong demand for the development of technologies that would allow for scale-up and a shortened reaction process time. Herein, we report that electrolysis was successfully accomplished using a flow-divided-electrochemical reactor within a few seconds, enabling the desired chemical conversion in a short period of time. Moreover, the narrow electrode gap of the flow reactor, which offers greener conditions than the conventional batch reactor, resulted in the continuous flash synthesis of C-arylglycosides.